110k views
3 votes
Someone please help!! Thanks!

Someone please help!! Thanks!-example-1
User Kenshi
by
5.2k points

1 Answer

6 votes

Answer:

n=2

Explanation:

2n+3+3n=n+11

Step 1: Simplify both sides of the equation.

2n+3+3n=n+11

(2n+3n)+(3)=n+11(Combine Like Terms)

5n+3=n+11

5n+3=n+11

Step 2: Subtract n from both sides.

5n+3−n=n+11−n

4n+3=11

Step 3: Subtract 3 from both sides.

4n+3−3=11−3

4n=8

Step 4: Divide both sides by 4.

after you do that you get the answer witch is

=2

User Bhuwansahni
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.